Open surgical repair of an abdominal aortic aneurysm during the second trimester of pregnancy - Ndeye Fatou Sow, MD; Abdoul Ahad Mbengue, MD; Jean Michel Davaine, MD, PhD; Morgane Lemierre, MD; Papa Adama Dieng, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
A 37-year-old obese woman, trigravida and secundiparous, at 17 weeks of gestation presented with acute abdominal pain. Doppler ultrasound examination showed an infrarenal abdominal aortic aneurysm measuring 61 mm in diameter and a computed tomography angiography outlined a fissured infrarenal aneurysm measuring 85 mm in diameter. To preserve the pregnancy, the obstetrician performed perioperative tocolysis. Subsequently, open surgery was conducted using open repair with 60 minutes of infrarenal cross-clamping. The postoperative course was uneventful, and the patient was discharged on day 10. She subsequently gave birth to a healthy baby at full term.